Governments Should Play Games: Towards a Framework for the Gamification of Civic Engagement Platforms. (April 2017) - Hassan, Lobna
Background. Gamification is concerned with the utilization ofmotivational affordances that create value-adding experience in thedesign of services . It has many applications in different fields and has been shown to be a good design methodology to influence motivation and behavioral change.Civic engagement and its online platforms could benefit from gamification, as these areas suffer from low engagement levels, thus defeating the purpose for which they are created. Purpose. There is a lack of understanding of how civic engagement platforms should be gamified to sustain active engagement and assist in community building, while also fulfilling their operational objectives. This article aims to provide a theoretical framework andguidelines for the gamification of civic engagement platforms. Contribution. Atheoretical framework for the gamification of civic engagement platforms is presented, drawing uponself-determination theory and democraticdeliberation theory . Through this work, we also identify future research directions and highlight the need for research on related subjects.